Antenatal Determinants of Bronchopulmonary Dysplasia and Late Respiratory Disease in Preterm Infants - Morrow, Lindsey A.; Wagner, Brandie D.; Ingram, David A.; Poindexter, Brenda B.; Schibler, Kurt; Cotten, C. Michael; Dagle, John; Sontag, Marci K.; Mourani, Peter M.; Abman, Steven H. (American journal of respiratory and critical care medicine, 2017)
Mechanisms contributing to chronic lung disease after preterm birth are incompletely understood. To identify antenatal risk factors associated with increased risk for bronchopulmonary dysplasia (BPD) and respiratory disease during early childhood after preterm birth, we performed a prospective, longitudinal study of 587 preterm infants with gestational age less than 34 weeks and birth weights between 500 and 1,250 g. Data collected included perinatal information and assessments during the neonatal intensive care unit admission and longitudinal follow-up by questionnaire until 2 years of age. After adjusting for covariates, we found that maternal smoking prior to preterm birth increased the odds of having an infant with BPD by twofold (P = 0.02). Maternal smoking was associated with prolonged mechanical ventilation and respiratory support during the neonatal intensive care unit admission. Preexisting hypertension was associated with a twofold (P = 0.04) increase in odds for BPD. Lower gestational age and birth weight z-scores were associated with BPD. Preterm infants who were exposed to maternal smoking had higher rates of late respiratory disease during childhood. Twenty-two percent of infants diagnosed with BPD and 34% of preterm infants without BPD had no clinical signs of late respiratory disease during early childhood. We conclude that maternal smoking and hypertension increase the odds for developing BPD after preterm birth, and that maternal smoking is strongly associated with increased odds for late respiratory morbidities during early childhood. These findings suggest that in addition to the BPD diagnosis at 36 weeks, other factors modulate late respiratory outcomes during childhood. We speculate that measures to reduce maternal smoking not only will lower the risk for preterm birth but also will improve late respiratory morbidities after preterm birth.